Subunit-Dependent High-Affinity Zinc Inhibition of Acid-Sensing Ion Channels - Chu, Xiang-Ping (Society for Neuroscience, 2004)
Acid-sensing ion channels (ASICs), a novel class of ligand-gated cation channels activated by protons, are highly expressed in peripheral sensory and central neurons. Activation of ASICs may play an important role in physiological processes such as nociception, mechanosensation, and learning-memory, and in the pathology of neurological conditions such as brain ischemia. Modulation of the activities of ASICs is expected to have a significant influence on the roles that these channels can play in both physiological and/or pathological processes. Here we show that the divalent cation Zn(2+), an endogenous trace element, dose-dependently inhibits ASIC currents in cultured mouse cortical neurons at nanomolar concentrations. With ASICs expressed in Chinese hamster ovary cells, Zn(2+) inhibits currents mediated by homomeric ASIC1a and heteromeric ASIC1a-ASIC2a channels, without affecting currents mediated by homomeric ASIC1β, ASIC2a, or ASIC3. Consistent with ASIC1a-specific modulation, high-affinity Zn(2+) inhibition is absent in neurons from ASIC1a knock-out mice. Current-clamp recordings and Ca(2+)-imaging experiments demonstrated that Zn(2+) inhibits acid-induced membrane depolarization and the increase of intracellular Ca(2+). Mutation of lysine-133 in the extracellular domain of the ASIC1a subunit abolishes the high-affinity Zn(2+) inhibition. Our studies suggest that Zn(2+) may play an important role in a negative feedback system for preventing overexcitation of neurons during normal synaptic transmission and ASIC1a-mediated excitotoxicity in pathological conditions.